Description and molecular characteristics of Morishitium polonicum malayense Urabe, Nor Hashim & Uni, n. subsp. (Trematoda: Cyclocoelidae) from the Asian glossy starling, Aplonis panayensis strigata (Passeriformes: Sturnidae) in Peninsular Malaysia - Urabe, Misako; Nor Hashim, Noorul Ezyan; Uni, Shigehiko; Iwaki, Takashi; Abdullah Halim, Muhammad Rasul; Marzuki, Mohammad Effendi; Mat Udin, Ahmad Syihan; Zainuri, Nur Afiqah; Omar, Hasmahzaiti; Agatsuma, Takeshi; Uga, Shoji; Takaoka, Hiroyuki; et al. (Elsevier, 2020)
We describe Morishitium polonicum malayense n. subsp. from Asian glossy starlings (Aplonis panayensis strigata) (Horsfield, 1821) (Passeriformis: Sturnidae) caught in Malaysia. The trematodes had parasitized the air sacs and the thoracic and body cavities of 40 out of 67 (59.7%) birds examined. The specimens each had an oral sucker, a postpharyngeal genital pore, and tandem testes, but lacked a ventral sucker. The morphological characteristics of our specimens were similar to those of M. polonicum polonicum (Machalska, 1980) from Poland. However, the anterior extremity of vitelline follicles of the present specimens sometimes extended to the level of pharynx. The oral sucker width, oral sucker width/pharynx width ratio, and intertesticular space metrics differed from those of M. p. polonicum. The maximum-likelihood trees based on the cytochrome c oxidase subunit I (COI) and the internal transcribed spacer 2 (ITS2) sequences indicated that the species from the present study formed a sister group with M. p. polonicum from the Czech Republic. The p-distances of COI and ITS2 sequences between the present specimens and M. p. polonicum from the Czech Republic were 6.9–7.5% and 0.6%, respectively. These genetic divergences indicate the border for intra- or interspecific variation of digeneans. The definitive host species and geographical distribution of the current specimens were distinct from those of M. p. polonicum from Europe. We thus concluded that the present specimens are ranked as a new subspecies of M. polonicum, namely M. polonicum malayense n. subsp. © 2020 Elsevier B.V.